Mixed Strategies in Discriminatory Divisible-good Auctions - Edward J. Anderson; Pär Holmberg; Andrew B. Philpott (Research Institute of Industrial Economics (IFN), 2009)
Author: Edward J. Anderson, Pär Holmberg and Andrew B. Philpott Keywords: Pay-as-bid Auction; Divisible Good Auction; Mixed Strategy Equilibria; Wholesale Electricity Markets Pages: 71 Published: November 24, 2009 JEL-codes: D43; D44; C72 Download Wp814.pdf (756 kB) Abstract Using the concept of market-distribution functions, we derive general optimality conditions for discriminatory divisible-good auctions, which are also applicable to Bertrand games and non-linear pricing. We introduce the concept of offer distribution function to analyze randomized offer curves, and characterize mixed-strategy Nash equilibria for pay-as-bid auctions where demand is uncertain and costs are common knowledge; a setting for which pure-strategy supply function equilibria typically do not exist. We generalize previous results on mixtures over horizontal offers as in Bertrand-Edgeworth games, but more importantly we characterize novel mixtures over partly increasing supply functions.
Keywords: C72; D43; D44; 330; Pay-as-bid Auction; Divisible Good Auction; Mixed Strategy Equilibria; Wholesale Electricity Markets; Auktion; Güter; Oligopol; Nichtkooperatives Spiel; Elektrizitätswirtschaft